Biochemical and haematological responses to thermal stress in Labeo rohita (Hamilton, 1822) fingerlings - Kumar, Prem; Pal, Asim K.; Sahu, Narottam P.; Christina, L.; Jha, Ashish Kumar (Indian Journal of Fisheries, 2019)
An experiment was conducted to understand the effect of thermal shock on stress and recovery in Labeo rohita (Hamilton, 1822) fingerlings. L. rohita fingerlings were exposed to a temperature of 380C for Â 2 h and permitted to recuperate afterwards for 48 h. Primary and secondary stress parameters were analysed after 2, 4, 8, 12, 24 and 48 h of recovery. The activity of glucose-6-phosphate dehydrogenase and acetylcholine esterase reduced significantly (p<0.05). Erythrocytes, haemoglobin, respiratory burst activity and lysozyme levels increased significantly (p<0.05) by 7.31, 23.91, 109.09 and 70.13% after thermal shock, whereas leucocytes, serum protein, albumin and globulin showed a reverse trend. During recovery, biochemical parameters normalised in 48 h. However, immunological variables such as serum total protein, albumin and globulin, and histopathological changes in gill and kidney tissues did not return to normal condition. Kewwords:Â Enzymes, Haematology, Histopathology, Labeo rohita, Stress recovery, Thermal stress